A Case of Non-Small Cell Lung Cancer with Possible “Disease Flare” on Nivolumab Treatment - Shotaro Chubachi; Hiroyuki Yasuda; Hidehiro Irie; Koichi Fukunaga; Katsuhiko Naoki; Kenzo Soejima; Tomoko Betsuyaku (Case Reports in Oncological Medicine)
Background. Recent clinical trials proven the clinically significant efficacy and tolerability of nivolumab, a programmed death 1 (PD-1) inhibitor, in previously treated patients with non-small cell lung cancer (NSCLC). Case Presentation. Here, we describe the case of a patient who experienced possible “disease flare” immediately after initiation of nivolumab treatment. A 54-year-old man was diagnosed with Stage IIB (T2N1M0) lung adenocarcinoma. After 7 years from recurrence, 10th line chemotherapy, nivolumab, was initiated. Six weeks later, after 3 cycles of nivolumab treatment, rapid lung cancer progression was observed with an increase in the size of the primary lesion, multiple novel nodules on both lungs, and multiple novel brain metastases. Conclusion. We believe that physicians should be made aware that, in a subset of NSCLC patients, disease flare might occur on nivolumab treatment.